PENGARUH INTEGRATED MARKETING COMMUNICATION TERHADAP BRAND EQUITY PERBANKAN SYARIAH DI KOTA MALANG - Rahayu, Yayuk Sri (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2013)
This research aimed to know the influence of integrated marketing communication to brand equity of sharia banking at Malang simoultaneusly and partially. Used 102 respondents with accidental sampling method and data was analized by multiple linier regression. The result shows, first, integrated marketing communication influenced simoultaneusly to brand equity of sharia banking at Malang. Second, only one variable that influenced partially to brand equity of sharia banking at Malang, the variable is public relation. So there is not dominant variable. Â